Transient Receptor Potential Vanilloid 1 Antagonists Prevent Anesthesia-induced Hypothermia and Decrease Postincisional Opioid Dose Requirements in Rodents. (November 2017) - Garami, Andras; Ibrahim, Mohab; Gilbraith, Kerry; Khanna, Rajesh; Pakai, Eszter; Miko, Alexandra; Pinter, Erika; Romanovsky, Andrej A.; Porreca, Frank; Patwardhan, Amol M.
Abstract : Background: Intraoperative hypothermia and postoperative pain control are two important clinical challenges in anesthesiology. Transient receptor potential vanilloid 1 has been implicated both in thermoregulation and pain. Transient receptor potential vanilloid 1 antagonists were not advanced as analgesics in humans in part due to a side effect of hyperthermia. This study tested the hypothesis that a single, preincision injection of a transient receptor potential vanilloid 1 antagonist could prevent anesthesia-induced hypothermia and decrease the opioid requirement for postsurgical hypersensitivity. Methods: General anesthesia was induced in rats and mice with either isoflurane or ketamine, and animals were treated with transient receptor potential vanilloid 1 antagonists (AMG 517 or ABT-102). The core body temperature and oxygen consumption were monitored during anesthesia and the postanesthesia period. The effect of preincision AMG 517 on morphine-induced reversal of postincision hyperalgesia was evaluated in rats. Results: AMG 517 and ABT-102 dose-dependently prevented general anesthesia-induced hypothermia (mean ± SD; from 1.5° ± 0.1°C to 0.1° ± 0.1°C decrease; P < 0.001) without causing hyperthermia in the postanesthesia phase. Isoflurane-induced hypothermia was prevented by AMG 517 in wild-type but not in transient receptor potential vanilloid 1 knockout mice (n = 7 to 11 per group). The prevention of anesthesia-induced hypothermia by AMG 517 involved activation of brown fat thermogenesis with a possible contribution from changes in vasomotor tone. A single preincision dose of AMG 517 decreased the morphine dose requirement for the reduction of postincision thermal (12.6 ± 3.0 vs. 15.6 ± 1.0 s) and mechanical (6.8 ± 3.0 vs. 9.5 ± 3.0 g) withdrawal latencies. Conclusions: These studies demonstrate that transient receptor potential vanilloid 1 antagonists prevent anesthesia-induced hypothermia and decrease opioid dose requirements for the reduction of postincisional hypersensitivity in rodents. Abstract : The selective transient receptor potential vanilloid 1 antagonists AMG 517 and ABT-102 dose-dependently prevented hypothermia during general anesthesia in rats. These same drugs reduced incisional nociceptive sensitization.Supplemental Digital Content is available in the text.